The Effect of Pre-Anesthesia Assessment on Patient Safety in the Operating Room - Saputra, Nopan; Sari, Yance Komela; Febristi, Anisa (Universitas Baiturrahmah, 2024)
Background: The development of the science of anesthesia provides consideration in administering the type of anesthesia used. The pre-anesthesia assessment is the basis for planning the findings on the monitor during and after anesthesia. The completeness of the pre-anesthesia assessment has an important role in patient safety, if the anesthetic assessment is not properly completed it allows errors in the operation process. Patient safety goals are the main requirement to be implemented in all hospitals accredited by KARS. Patient safety goals intend to drive specific improvements in patient safety. This goal highlights problematic areas of health care. The wrong-site, wrong procedure and wrong-patient surgery are something that is worrying and not uncommon in the hospital. This error resulted from ineffective communication between members of the surgical team, not involving the patient in site marking, and no procedure for verifying the surgical site. Objective: The study aims to see the effect of the completeness of the pre-anesthesia assessment on patient safety. Methods: The research design is a cross-sectional study. The population in this study were patients who underwent surgery with a total sample of 70 people. Data processing through the stages of editing, coding, entry, and cleaning. Univariate analysis and bivariate analysis used the chi-square test with a 95% degree of confidence α = 0.05. Results: The results showed that the completeness of the pre-anesthesia assessment was complete with a percentage of 88.6%. Good patient safety with a percentage of 65.7%. There was no significant relationship between the completeness of the pre-anesthesia assessment and patient safety (p=0.076). Conclusions: To improve the implementation of pre-anesthesia assessments, hospitals need to review the completeness of filling out pre-anesthesia assessments by anesthesiologists before patients are operated on, to prevent errors in improving patient safety. Prepare facilities and infrastructure for the needs of patient safety programs by accreditation standards.